Control of Multiple Herbicide-Resistant Palmer Amaranth in Enlist Corn - R. Liu; V. Kumar; T. Lambert (Kansas Agricultural Experiment Station Research Reports, 2020)
Recent evolution of multiple herbicide resistant (MHR) Palmer amaranth [resistant to 2,4-D, glyphosate (Roundup), chlorsulfuron (Glean), atrazine (Aatrex), and mesotrione (Callisto)] is a serious threat to newly developed stacked trait technologies, including Enlist crops (tolerant to 2,4-D, glyphosate, and glufosinate). Field experiments were conducted in 2019 at the Kansas State University Agricultural Research Center near Hays, KS, to determine the effectiveness of various preemergence (PRE) followed by (fb) postemergence (POST) herbicides (multiple modes of action) for controlling this MHR Palmer amaranth in Enlist corn. The study was established in no-till dryland wheat stubble where MHR Palmer amaranth seeds were uniformly infested. All PRE treatments included Roundup at 32 oz/a to control volunteer wheat seedlings at the time of corn planting. Treatments were arranged in a randomized complete block design, with four replications. Herbicides were applied using a handheld boom sprayer calibrated to deliver 15 GPA. Data on percent visual control of MHR Palmer amaranth were recorded biweekly throughout the season, and corn grain yield was recorded at harvest. All PREfbPOST herbicide programs—except PRE applied Armezon Pro plus Aatrexfba POST treatment of Roundup + Enlist One + Liberty, and a sequential PREfbPOST treatment of Roundup + Enlist One + Liberty—provided excellent, season-long control (92-96%) of MHR Palmer amaranth. In contrast, end-season control of MHR Palmer amaranth did not exceed 85% with PRE applied Armezon Pro plus Aatrexfba POST treatment of Roundup + Enlist One + Liberty, and a sequential PREfbPOST treatment of Roundup + Enlist One + Liberty. Corn grain yields were significantly improved among all the tested herbicide programs compared to the nontreated weedy check plots. These results indicate that the effective PREfbPOST (two pass) programs evaluated in this study can be utilized for effective management of MHR Palmer amaranth in Enlist corn.
Keywords: Multiple herbicide resistance; Palmer amaranth; Enlist corn